2021
DOI: 10.3390/ijerph18147597
|View full text |Cite
|
Sign up to set email alerts
|

Organizational-Level Moderators Impacting Tobacco-Related Knowledge Change after Tobacco Education Training in Substance Use Treatment Centers

Abstract: Tobacco use is disproportionately elevated among patients with substance use disorders relative to the general U.S. population. Tobacco interventions are lacking within substance use treatment centers (SUTCs) due to lack of knowledge and training. This study examined knowledge gain and the organizational factors that might moderate knowledge gains following tobacco education training provided to employees (N = 580) within 15 SUTCs that were participating in a tobacco-free workplace program. The number of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 42 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…Other studies suggest that increasing clinicians’ provision of evidence-based interventions may increase quit attempts and promote reduced tobacco use during treatment among patients with substance use disorders who smoke [ 28 , 32 ]. Thus, the present results add to the literature supporting the implementation of these programs to expand a substance use treatment center’s capacity to screen for and intervene on tobacco use, which may ultimately affect the tobacco use and tobacco-related disease inequities among individuals with substance use disorders [ 15 , 23 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 44 ]. Results also demonstrated that organizational readiness for change moderated these changes in intervention delivery; specifically, substance use treatment centers with greater initial Change Efficacy demonstrated greater increases in Asking about tobacco use, whereas substance use treatment centers with lower Resource Availability demonstrated greater increases in Asking about tobacco use as well as Assessing willingness to quit tobacco.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Other studies suggest that increasing clinicians’ provision of evidence-based interventions may increase quit attempts and promote reduced tobacco use during treatment among patients with substance use disorders who smoke [ 28 , 32 ]. Thus, the present results add to the literature supporting the implementation of these programs to expand a substance use treatment center’s capacity to screen for and intervene on tobacco use, which may ultimately affect the tobacco use and tobacco-related disease inequities among individuals with substance use disorders [ 15 , 23 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 44 ]. Results also demonstrated that organizational readiness for change moderated these changes in intervention delivery; specifically, substance use treatment centers with greater initial Change Efficacy demonstrated greater increases in Asking about tobacco use, whereas substance use treatment centers with lower Resource Availability demonstrated greater increases in Asking about tobacco use as well as Assessing willingness to quit tobacco.…”
Section: Discussionmentioning
confidence: 59%
“…Of these substance use treatment centers, many served unique populations, such as individuals who are experiencing homelessness, vulnerably housed, pregnant, and/or involved with the criminal justice system. These characteristics of the substance use treatment centers are described further in a separate study [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work will need to assess the impacts of this program on the sustainment of all evidence-based tobacco use policies and practices as associated with a comprehensive tobacco-free workplace program (e.g., compliance with the tobacco-free workplace policy, provision of tobacco screening and treatment to patients), which was beyond the scope and timeline of the underlying grant. However, results speak to the potential upkeep of one major component of the TTTF comprehensive tobacco-free workplace program: the provision of employee education about addressing tobacco use amongst their behavioral health patients, which has previously been associated with increased screening and treatment of tobacco use [ 15 , 22 , 23 , 24 ]. An important future direction of this work is to evaluate whether TTTF’s train-the-trainer program’s implementation was linked with clinician behavior change and, ultimately, reduced patient tobacco use rates.…”
Section: Discussionmentioning
confidence: 99%
“…An example item was, “Which of the following is NOT one of the “5As” or tobacco cessation brief intervention?” with answer options (a) ask; (b) arrange; (c) assess; and (d) allow. This measure has been used in our prior work [ 12 , 15 , 22 , 23 , 24 ]. No personally identifying information about the employee was collected on this survey at either administration.…”
Section: Methodsmentioning
confidence: 99%